Elastic sandwich-type GaN/MnO2/MnON composites for flexible supercapacitors with high energy density. Issue 27 (21st June 2018) - Wang, Shouzhi; Shao, Yongliang; Liu, Weikang; Wu, Yongzhong; Hao, Xiaopeng
Abstract : A novel flexible electrode with a sandwich structure consisting of double stabilizing buffer layers is designed and fabricated for the first time, and significant improvement in cycling stability and desired areal capacity is achieved. This strategy will allow large volume change metal oxide electrodes to be applied in energy storage and related fields. Abstract : Metal oxides as supercapacitor (SC) electrode materials possess high capacitance and energy density, however, the low electrical conductivity and structural weakness resulting from volume shrinkage and expansion during the energy storage process seriously hinder their rate capabilities and cycling performances. Herein, we design and fabricate a metal nitride/metal oxide/metal oxynitride elastic sandwich structure nanohybrid with double stabilizing buffer layers for the first time. This unique hierarchical structure not only provides a highly conductive network and intimate contacts between carbon fiber (CF)/GaN and MnO2 /Mn oxynitride (MnON) for effective charge transportation, but also offers synergistic physical restriction and chemical confinement of volume change during charge/discharge processes. Therefore, these conductive GaN/MnO2 /MnON compact films used directly as an electrode possess a high areal capacitance of 1915.5 mF cm −2 (532.1 mA h cm −2 ) at 0.1 mA cm −2 . A flexible symmetric supercapacitor device based on the GaN/MnO2 /MnON hybrid electrode exhibits outstanding energy output efficiency (achieved energy density of 0.76 mW h cm −3 ), high capacity retention rate (95.5% capacity was retained after 10 000 cycles) and remarkable flexibility, showing its attractive prospect in wearable electronics and sustainable energy application. This design strategy provides an efficient way to apply large volume change metal oxide materials to energy storage and conversion devices.